Negative electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
The use of a zinc-manganese alloy as the negative electrode active material in secondary batteries addresses the inefficiencies of existing zinc-based systems, enhancing both initial and subsequent discharge capacity.
Patent Information
- Application Number
- JP2021551286
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-29
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-09-29
AI Technical Summary
Existing zinc-based negative electrode composite layers in secondary batteries exhibit low initial charge-discharge efficiency and insufficient discharge capacity, particularly in the first cycle, limiting their overall performance.
Employing a zinc-manganese alloy with a general formula MnZn x (3≦x≦13) as the negative electrode active material, which enhances the initial charging and discharging efficiency and increases discharge capacity even after the second cycle.
The zinc-manganese alloy improves the initial charging and discharging efficiency of secondary batteries, leading to higher discharge capacity and better cycle characteristics.
Smart Images

Figure 0007617514000002 
Figure 0007617514000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode active material for a nonaqueous electrolyte secondary battery, and a nonaqueous electrolyte secondary battery. [Background technology]
[0002] Various alloys other than Si are being considered as negative electrode active materials for high-capacity secondary batteries. For the purpose of increasing the capacity of secondary batteries and improving their charge-discharge cycle characteristics, Patent Document 1 discloses TiZn, and Patent Document 2 discloses NiZn, CuZn, and FeZn. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-79470 A [Patent Document 2] JP 2013-51170 A Summary of the Invention
[0004] In the secondary batteries using the zinc alloys disclosed in Patent Documents 1 and 2 as the negative electrode composite layer, it was found that in the first charge / discharge cycle, a sufficient discharge capacity was not obtained relative to the charge capacity, and the initial charge / discharge efficiency was low.
[0005] The negative electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure has the general formula MnZn x This includes zinc-manganese alloys represented by the formula (3≦x≦13).
[0006] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a negative electrode containing the above-described negative electrode active material for nonaqueous electrolyte secondary batteries, a positive electrode, and a nonaqueous electrolyte.
[0007] According to one embodiment of the present disclosure, the initial charge / discharge efficiency of a secondary battery can be improved, and therefore the discharge capacity can be increased even in the second cycle and thereafter. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a longitudinal sectional view of a nonaqueous electrolyte secondary battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In order to increase the capacity of secondary batteries, a negative electrode active material in which Si is mixed with graphite is used. However, Si is expensive, and the inclusion of Si may deteriorate the cycle characteristics of secondary batteries, so various alloys other than Si are attracting attention as negative electrode active materials. For example, for the purpose of increasing the capacity of secondary batteries and improving the charge / discharge cycle characteristics, Patent Document 1 discloses TiZn, and Patent Document 2 discloses NiZn, CuZn, and FeZn. However, as a result of the study by the present inventors, it was found that in secondary batteries in which the zinc alloys disclosed in Patent Documents 1 and 2 are used as negative electrode composite layers, sufficient discharge capacity is not obtained relative to the charge capacity in the first cycle of charge / discharge, and the initial charge / discharge efficiency is low, whereas the zinc manganese alloy according to the present disclosure has a high initial charge / discharge efficiency and can increase the discharge capacity even in the second cycle and thereafter. General formula MnZn x The zinc-manganese alloy represented by (3≦x≦13) absorbs Li, and when it is charged, Zn and Li combine to become LiZn, and when it is discharged, Zn and Mn recombine to release Li. Since the zinc-manganese alloy has a lower melting point than other zinc alloys such as TiZn, NiZn, CuZn, and FeZn, it is thought that Mn moves easily in Zn, and it is presumed that the Li absorbed in the negative electrode in the first cycle can be efficiently released by discharging.
[0010] Hereinafter, an example of an embodiment of the negative electrode active material for nonaqueous electrolyte secondary batteries according to the present disclosure and a nonaqueous electrolyte secondary battery using the negative electrode active material will be described in detail. Hereinafter, a cylindrical battery in which a wound electrode body is housed in a bottomed cylindrical exterior can is exemplified, but the exterior can is not limited to a cylindrical exterior can, and may be, for example, a rectangular exterior can, or an exterior made of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body may be a laminated type electrode body in which multiple positive electrodes and multiple negative electrodes are alternately laminated with separators interposed therebetween.
[0011] FIG. 1 is a longitudinal cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. In the secondary battery 10 shown in FIG. 1, an electrode body 14 and a non-aqueous electrolyte (not shown) are housed in an exterior body 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. As a non-aqueous solvent (organic solvent) for the non-aqueous electrolyte, carbonates, lactones, ethers, ketones, esters, etc. can be used, and these solvents can be used in a mixture of two or more kinds. When using a mixture of two or more kinds of solvents, it is preferable to use a mixed solvent containing a cyclic carbonate and a chain carbonate. For example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used as the cyclic carbonate, and dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc. can be used as the chain carbonate. The electrolyte salt of the non-aqueous electrolyte may be LiPF6, LiBF4, LiCF3SO3, or a mixture thereof. The amount of electrolyte salt dissolved in the non-aqueous solvent may be, for example, 0.5 to 2.0 mol / L. For convenience of explanation, the sealing body 16 side will be referred to as "upper" and the bottom side of the exterior body 15 as "lower".
[0012] The opening end of the exterior body 15 is closed with the sealing body 16, so that the inside of the secondary battery 10 is sealed. Insulating plates 17 and 18 are provided above and below the electrode body 14, respectively. The positive electrode lead 19 extends upward through the through hole of the insulating plate 17 and is welded to the underside of the filter 22, which is the bottom plate of the sealing body 16. In the secondary battery 10, the cap 26, which is the top plate of the sealing body 16 electrically connected to the filter 22, serves as the positive electrode terminal. On the other hand, the negative electrode lead 20 extends through the through hole of the insulating plate 18 to the bottom side of the exterior body 15 and is welded to the inner bottom surface of the exterior body 15. In the secondary battery 10, the exterior body 15 serves as the negative electrode terminal. In addition, when the negative electrode lead 20 is installed at the terminal portion, the negative electrode lead 20 passes outside the insulating plate 18, extends to the bottom side of the exterior body 15, and is welded to the inner bottom surface of the exterior body 15.
[0013] The exterior body 15 is, for example, a cylindrical metal exterior can with a bottom. A gasket 27 is provided between the exterior body 15 and the sealing body 16 to ensure the sealing of the inside of the secondary battery 10. The exterior body 15 has a grooved portion 21 that supports the sealing body 16 and is formed, for example, by pressing a side portion from the outside. The grooved portion 21 is preferably formed in an annular shape along the circumferential direction of the exterior body 15, and supports the sealing body 16 on its upper surface via the gasket 27.
[0014] The sealing body 16 includes a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cap 26, which are stacked in this order from the electrode body 14 side. Each member constituting the sealing body 16 has, for example, a disk shape or a ring shape, and each member except the insulating member 24 is electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective centers, and the insulating member 24 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, for example, the lower valve body 23 breaks, and as a result, the upper valve body 25 swells toward the cap 26 and separates from the lower valve body 23, thereby cutting off the electrical connection between them. When the internal pressure further increases, the upper valve body 25 breaks, and gas is discharged from the opening 26a of the cap 26.
[0015] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the negative electrode active material that constitutes the negative electrode 12, will be described in detail below.
[0016] [Positive electrode] The positive electrode 11 has a positive electrode core and a positive electrode composite layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film with the metal disposed on the surface, or the like can be used. The thickness of the positive electrode core is, for example, 10 μm to 30 μm. The positive electrode composite layer contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both sides of the positive electrode core except for the part to which the positive electrode lead 19 is connected. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, and the like to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode composite layer on both sides of the positive electrode core.
[0017] The positive electrode active material contains lithium transition metal oxide as a main component. The positive electrode active material may be substantially composed of only lithium transition metal oxide, or may be a material in which inorganic compound particles such as aluminum oxide and lanthanoid-containing compounds are fixed to the surface of lithium transition metal oxide particles. The lithium transition metal oxide may be used alone or in combination of two or more kinds.
[0018] Examples of metal elements contained in the lithium transition metal oxide include nickel (Ni), cobalt (Co), manganese (Mn), aluminum (Al), boron (B), magnesium (Mg), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), gallium (Ga), strontium (Sr), zirconium (Zr), niobium (Nb), indium (In), tin (Sn), tantalum (Ta), and tungsten (W). An example of a suitable lithium transition metal oxide is represented by the general formula: Li α Ni x M (1―x) O2 (0.1≦α≦1.2, 0.3≦x<1, M contains at least one of Co, Mn, and Al).
[0019] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, carbon nanotubes, carbon nanofibers, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salts, and polyethylene oxide (PEO).
[0020] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode 12, a film with the metal disposed on the surface layer, or the like can be used. The thickness of the negative electrode core is, for example, 5 μm to 15 μm. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the part to which the negative electrode lead 20 is connected. The negative electrode 12 can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core. A conductive material may also be added to the negative electrode composite slurry. The conductive material can make the conductive path uniform.
[0021] The binder contained in the negative electrode mixture layer can be fluororesin, PAN, polyimide resin, acrylic resin, polyolefin resin, etc., as in the case of the positive electrode 11. When preparing the mixture slurry using an aqueous solvent, it is preferable to use CMC or a salt thereof, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol, etc. Examples of the conductive material contained in the negative electrode mixture layer include carbon black, acetylene black, ketjen black, carbon nanotubes, and carbon nanofibers.
[0022] The negative electrode active material has the general formula MnZn x(3≦x≦13). This can improve the initial charge / discharge efficiency of the secondary battery. The range of the value of x is more preferably 6≦x≦10. x The zinc-manganese alloy represented by (3≦x≦13) may contain impurity elements such as Ca, Mg, Fe, Si, and Cd that are present in the raw materials or mixed in during the manufacturing process. In other words, the negative electrode active material has a composition excluding the impurity elements that is represented by the general formula MnZn x The zinc-manganese alloy is represented by (3≦x≦13). The content of impurity elements is preferably 500 ppm or less, more preferably 100 ppm or less, and particularly preferably 50 ppm or less. The mole fraction of each element contained in the negative electrode active material is measured by inductively coupled plasma (ICP) emission spectrometry. The general formula is MnZn x The zinc-manganese alloy represented by (3≦x≦13) is, for example, a γ phase having a structure of MnZn4, a δ phase having a structure of MnZn9, and a MnZn 13 The ζ phase is electrochemically active and particularly contributes to improving charge / discharge efficiency. The zinc-manganese alloy may contain phases other than the γ phase, δ phase, and ζ phase, and may contain, for example, an amorphous portion. The negative electrode active material may be used alone or in combination of two or more types. For example, one type of zinc-manganese alloy, MnZn x Two or more kinds of MnZn with different values of x may be used. x A mixture of the above may be used. A zinc-manganese alloy and a negative electrode active material other than the zinc-manganese alloy may be used in combination. The negative electrode active material other than the zinc-manganese alloy is not particularly limited as long as it can reversibly absorb and release lithium ions, and examples of the negative electrode active material that can be used include graphite (natural graphite, artificial graphite), silicon (Si), tin (Sn), and other metals that can be alloyed with lithium, and oxides containing metal elements such as Si and Sn.
[0023] The zinc-manganese alloy is a particle having a volume-based median diameter (D50) of, for example, 1 μm or more and 100 μm or less, preferably 50 μm or less, and particularly preferably 30 μm or less. The D50 of the zinc-manganese alloy is preferably small because the distance that Li moves within the particle is shortened. The D50 of the zinc-manganese alloy can be made small by pulverizing with a ball mill. D50 means the particle size at which the cumulative frequency in the volume-based particle size distribution is 50% from the smallest particle size, and is also called the median diameter. The particle size distribution of the lithium transition metal oxide can be measured using a laser diffraction particle size distribution measuring device (for example, MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as the dispersion medium.
[0024] The zinc-manganese alloy can be produced by mixing Zn and Mn in a desired ratio, pelletizing the mixture, and then pulverizing the pellets after heat treatment. For example, the heat treatment temperature is 200°C to 600°C, and the heat treatment time is 0.5 hours to 12 hours.
[0025] The negative electrode active material has the general formula MnZn x In addition to the zinc-manganese alloy represented by (3≦x≦13), the zinc-manganese alloy further contains graphite, and the ratio of the zinc-manganese alloy to the number of moles of graphite is preferably 3 mol% to 30 mol%. By using graphite and the zinc-manganese alloy in this ratio, the graphite forms voids in the negative electrode mixture layer, allowing the electrolyte to permeate to the negative electrode core, while the zinc-manganese alloy increases the capacity of the battery.
[0026] The negative electrode 12 is manufactured by the method of the general formula MnZn x There is no particular limitation as long as the negative electrode active material contains a zinc-manganese alloy represented by (3≦x≦13). As described above, in addition to forming a negative electrode composite layer by applying and drying the negative electrode composite slurry, a zinc-manganese alloy may be formed on the surface of the negative electrode core by, for example, MnZn alloy plating, and if necessary, a heat treatment may be performed. For example, the heat treatment temperature is 200° C. to 600° C., and the heat treatment time is 1 minute to 60 minutes. In this case, the MnZn alloy plating layer becomes the negative electrode composite layer. Also, graphite may be laminated on the surface of the MnZn alloy plating layer.
[0027] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous membrane, a woven fabric, and a nonwoven fabric. The separator 13 is preferably made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer containing a heat-resistant material may be formed on the surface of the separator 13. Examples of the heat-resistant material include polyamide resins such as aliphatic polyamides and aromatic polyamides (aramids), and polyimide resins such as polyamideimides and polyimides.
[0028] <Example> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0029] <Example 1> [Synthesis of negative electrode active material] Mn and Zn were used as raw material powders, mixed in a molar ratio of Mn:Zn = 1:10, pelletized, and heat-treated at 400°C for 6 hours to produce MnZn 10 The zinc-manganese alloy was crushed to obtain MnZn 10 obtained.
[0030] [Preparation of negative electrode] Next, the MnZn 10 Acetylene black as a conductive material and polyvinylidene fluoride as a binder were prepared in a mass ratio of 92:5:3, and this was mixed with an N-methyl-2-pyrrolidone (NMP) solution to prepare a slurry. This slurry was applied to an aluminum negative electrode core having a thickness of 15 μm, and dried in an electric furnace maintained at 100° C. to form a negative electrode active material layer. After drying, the negative electrode core was rolled using a roller and punched out to produce a pellet-shaped electrode.
[0031] [Preparation of counter electrode] In order to investigate the characteristics of the negative electrode active material for lithium-ion secondary batteries, metallic lithium (Li) was used as the counter electrode instead of the above-mentioned positive electrode. Generally, in lithium-ion secondary batteries, lithium transition metal oxides such as LiNiO2 (which generally contain transition metals such as Co, Mn, and Ni) are used as the positive electrode active material. However, in this case, in order to investigate the characteristics of the negative electrode active material itself that does not depend on the positive electrode active material, a lithium metal foil was punched out and used as the counter electrode instead of the positive electrode active material generally used for electrodes. This type of method is often used to evaluate active materials.
[0032] [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte solution, which is a liquid non-aqueous electrolyte, was prepared by dissolving 1.0 mol / L of LiPF6 as an electrolyte salt in a non-aqueous solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:3.
[0033] [Battery construction] Using the negative electrode and nonaqueous electrolyte prepared as described above, a coin-type lithium ion secondary battery (hereinafter, coin-type battery) was prepared by the following procedure. A lithium metal foil serving as a counter electrode was pressed onto the inside of the bottom of a coin-type battery exterior body made of steel and consisting of a lid and a bottom, and a polyethylene microporous membrane separator impregnated with electrolyte, a negative electrode, a steel circular backing plate, and a disc spring were arranged and housed on top of the lithium metal foil in this order. The lid was then placed on the battery exterior body and the battery exterior body was crimped to seal, obtaining a coin-type battery.
[0034] <Comparative Example 1> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that only Zn was used as the raw material powder, and the Zn produced by pelletizing and heat-treating the pellet at 400°C for 6 hours was pulverized to obtain Zn having a volume-based median diameter (D50) of 20 μm.
[0035] <Comparative Example 2> The raw material powders were Ti and Zn, mixed in a molar ratio of Ti:Zn = 1:10, pelletized, and heat-treated at 415°C for 12 hours to produce TiZn. 10is pulverized to obtain TiZn 10 A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the above was obtained.
[0036] <Comparative Example 3> Co and Zn were used as raw material powders, mixed in a molar ratio of Co:Zn = 1:10, pelletized, and heat-treated at 415°C for 12 hours to produce CoZn. 10 is crushed to obtain CoZn 10 A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the above was obtained.
[0037] <Comparative Example 4> Ni and Zn were used as raw material powders, mixed in a molar ratio of Ni:Zn = 1:10, pelletized, and heat-treated at 415°C for 12 hours to produce NiZn. 10 is crushed to obtain NiZn 10 A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the above was obtained.
[0038] <Comparative Example 5> Cu and Zn were used as raw material powders, mixed in a molar ratio of Cu:Zn = 1:10, pelletized, and heat-treated at 415°C for 12 hours to produce CuZn. 10 is crushed to obtain CuZn with a volume-based median diameter (D50) of 20 μm. 10 A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the above was obtained.
[0039] The performance of each of the coin type batteries was evaluated by the following method, and the evaluation results are shown in Table 1. Table 1 shows the composition of the negative electrode active material together with the evaluation results.
[0040] [Evaluation of initial efficiency] The initial efficiency was evaluated by measuring the initial charge capacity and the initial discharge capacity for the coin type batteries of Example 1 and Comparative Examples 1 to 5. Discharge here refers to discharge in a battery in which the negative electrode active material of Example 1 and Comparative Examples 1 to 5 is combined with a commonly used positive electrode, such as LiNiO2. Here, since the coin type battery has a negative electrode as a working electrode and metallic lithium (Li) as a counter electrode, it should be called charging, but in accordance with the charge and discharge behavior of the negative electrode in a battery in which a commonly used positive electrode and a negative electrode are combined, the charge and discharge directions are expressed in the opposite direction. In other words, charging is to pass a current so as to lower the potential of the negative electrode, which is the working electrode, and discharging is to pass a current so as to raise the potential of the negative electrode, which is the working electrode.
[0041] First, charging was performed at a constant current of 0.05C until the battery voltage reached 0V, and then discharging was performed at a constant current of 0.05C until the battery voltage reached 1V, and the initial charge capacity and initial discharge capacity were measured. Note that the description of charge and discharge is written in the opposite order to the usual description as described above. That is, charging means passing a current so as to lower the potential of the working electrode until the battery voltage reaches 0V, and discharging means passing a current so as to raise the potential of the working electrode until the battery voltage reaches 1V. Based on the initial charge capacity and initial discharge capacity measured above, and the mass and density of the zinc alloy (zinc in Comparative Example 1) which is the negative electrode active material contained in the negative electrode mixture layer, the initial charge capacity density, initial discharge capacity density, and initial efficiency were calculated and evaluated using the following formula.
[0042] Initial charging capacity density (mAh / cm 3 ) = initial charge capacity (mAh) / mass of zinc alloy contained in the negative electrode mixture layer (g) × density of zinc alloy in the negative electrode mixture layer (g / cm 3 ) Initial discharge capacity density (mAh / cm 3 ) = initial discharge capacity (mAh) / mass of zinc alloy contained in the negative electrode mixture layer (g) × density of zinc alloy in the negative electrode mixture layer (g / cm 3 ) Initial efficiency (%) = initial discharge capacity / initial charge capacity x 100
[0043] [Table 1]
[0044] As shown in Table 1, the battery of Example 1 had a higher initial efficiency than the batteries of Comparative Examples 1 to 5. In addition, the battery of Example 1 also had a higher initial discharge capacity density than the batteries of Comparative Examples 1 to 5. From this result, it was found that by using a zinc-manganese alloy as the negative electrode active material, it is possible to improve the initial charge / discharge efficiency of the secondary battery, and to increase the discharge capacity even after the second cycle. [Explanation of symbols]
[0045] 10 Secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Exterior body 16 Sealing body 17,18 Insulating plate 19 Positive lead 20 Negative lead 21 Grooved part 22 Filters 23 Lower valve body 24 Insulating materials 25 Upper valve 26 Cap 26a opening 27 Gasket
Claims
1. General formula MnZn x A negative electrode active material for a non-aqueous electrolyte secondary battery, comprising a zinc-manganese alloy represented by the formula (3≦x≦13).
2. 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, further comprising graphite, wherein a ratio of the zinc-manganese alloy to a mole number of the graphite is 3 mol % to 30 mol %.
3. A negative electrode comprising the negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2; A positive electrode and A non-aqueous electrolyte; A non-aqueous electrolyte secondary battery comprising:
Citation Information
Patent Citations
Preparation method of hetaerolite nanoparticles used in lithium ion battery
CN103346306A
Zinc alkaline battery
JP1986051764A
Zinc alloy for electrochemical battery can
JP1993125470A
Hydrogen storage alloy, manufacture of hydrogen storage alloy and alkaline secondary battery
JP2000228191A
Nonaqueous electrolyte secondary battery
JP2012079470A